The 'civilising mission' of Portuguese colonialism, 1870-1930 - Jerónimo, Miguel Bandeira, 1973- (Cambridge imperial and post-colonial studies series., 2015)
This book provides an historical critical analysis of the doctrine of the 'civilising mission' in Portuguese colonialism in the crucial period from 1870 to 1930. Exploring international contexts and transnational connections, imperial politics and colonial policies, this 'civilising mission' is analysed and assessed by examining the contentious debates about the recruitment, employment and distribution of African manpower, namely over the persistence of slavery, the emergence and legalisation of 'conditions analogous to slavery', and of other modalities of compulsory labour.